A method of hard X‐ray phase‐shifting digital holography. (21st June 2016) - Park, So Yeong; Hong, Chung Ki; Lim, Jun
Abstract : Phase measurement in hard X‐ray phase shifting digital holography is demonstrated. Abstract : A new method of phase‐shifting digital holography is demonstrated in the hard X‐ray region. An in‐line‐type phase‐shifting holography setup was installed in a 6.80 keV hard X‐ray synchrotron beamline. By placing a phase plate consisting of a hole and a band at the focusing point of a Fresnel lens, the relative phase of the reference and objective beams could be successfully shifted for use with a three‐step phase‐shift algorithm. The system was verified by measuring the shape of a gold test pattern and a silica sphere.